Update on the Management of Morbid Adherent Placenta (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Morbid adherent placenta collectively includes placenta accrete, increta, and percreta, according to the depth of invasion through the decidua-myometrial junction. Incidence is increasing due to increase in the incidence of scarred uterus. Scarred either due to caesarean section, myomectomy or repeated D&C. These conditions are responsible for massive obstetrics haemorrhage, associated complications like consumption coagulopathy, multisystem organ failure & death. Also there is a risk for peripartum surgical complication, such as injury to the bladder, ureter & bowel. There is also the need for relaparotomy, complication of blood transfusion, admission in intensive care unit. Indicated or emergency preterm delivery needs admission of the newborn to neonatal intensive care unit. Outcome can be improved by multi disciplinary expertise and experienced approach for delivery, including the conservative management to avoid peripartum hysterectomy. Such team approach by maternal-fetal medicine, gynaecological surgeon, vascular, trauma, urology surgeon, transfusion medicine, intensivist, neonatologist, intervention radiologist, anaesthesiologist, specialized nursing staff and ancillary personnel.J Bangladesh Coll Phys Surg 2019; 37(1): 30-34